PCD no mercado de trabalho - SILVA, Edilaine Cristina Dias Araújo da; SILVA, Rosana Cristina da; CRISTINO, Samara Belisaria (060, 2024)
De acordo com o ministério do trabalho e emprego, existem 375 mil trabalhadores com deficiência no mercado de trabalho. Tendo em vista que os números de PCDs é de quase 19 milhões, nos questionamos o porquê dessa diferença gritante, a questão social interfere diretamente nesses números. Os principais fatores são: analfabetismo, falta de oportunidades, falta de acessibilidade. Na presente pesquisa, o Nordeste é onde se encontra o maior número de PCDs, os aspectos geográficos impactam esses números. Infelizmente no Brasil, falta infraestruturas para o PCD conseguir melhorar sua qualidade de vida.

According to the Ministry of Labor and Employment, there are 375 thousand workers with disabilities in the job market. Considering that the PCDS numbers are almost 19 million, we wonder why this is a stark difference. The social issue directly interferes with these numbers. The main factors are Illiteracy, lack of opportunities, lack of accessibility. In the present research, the northeast is where the largest number of PCDS are found, geographical aspects impact these numbers. Unfortunately, in Brazil, there is a lack of infrastructure for PWD to improve their quality of life.
PCD in the job market
Keywords: Administração; Gestão e Negócios